Generator Ganda Pada Pembangkit Listrik Mikrohidro Dengan Turbin Tunggal - Puji Ristianto; Sunardi Sunardi (Aviation Electronics, Information Technology, Telecommunications, Electricals, Controls (AVITEC), 2019)
Micro Hydro Power Plant (PLTMH) is one way to provide electricity, especially for remote areas far from the PLN network.PLTMH utilizes the flow of water to produce electricity. The purpose of this study is to increase the power produced by utilizing two generators that are installed in parallel with the gear box and pulley positions adjusted.This study uses two generators, namely generator A and generator B with a capacity of 3kVA per generator.Data retrieval is done in two ways, namely by loading and without burden. The method of loading is to add a load of incandescent light.Whereas no load is carried out by measuring the output voltage only.Based on this study, the results obtained were at generator A of 225 volts with pulley rotational speed of 2584 rpm.While the results on generator B amounted to 185 volts with pulley rotating speed of 1765 rpm.